Too much of a good thing? Affective empathy modulates the link between maladaptive coping and internalizing problems in children - Yu, Meryl (2024)
Empathy is widely seen as a strength and is the focus of social-emotional learning globally. Yet, the ‘too-much-of-a-good-thing’ principle posits that positive resources are rarely universally beneficial; rather, under specific boundary conditions, harms may be generated. We shed light on whether empathy is helpful or harmful in the maintenance cycle of psychopathology. To this end, we examined whether empathy moderates the relationship linking maladaptive coping with internalising and externalising problems one year later. We used longitudinal data of 98 (48% girls) mother-child dyads from Singapore’s largest birth cohort. Mothers rated children’s cognitive (CE) and affective empathy (AE) with Griffith Empathy Scale at age 4.5. Children self-rated maladaptive coping at age 11 with Cognitive Emotion Regulation Questionnaire, and internalising and externalising problems with Strengths and Difficulties Questionnaire at age 12. Separate linear regression analyses were conducted, controlling for child gender, internalising or externalising problems (age 4) and socioeconomic status (baseline). There was a significant interaction of AE with self-blame, rumination, and catastrophising, on internalising problems (B=0.03, 0.020, 0.02, SE=0.009, 0.01, 0.009, ps<.05). Specifically, only when coupled with high and moderate levels of AE, self-blame (B=0.52, 0.24, SE=0.12, 0.08, ps<.001), rumination (B=0.42, 0.21, SE=0.14, 0.09, ps<.05), and catastrophising (B=0.48, 0.22, SE=0.13, 0.08, ps<.05) positively predicted internalising problems one year later. No significant main or interaction effects were found for cognitive empathy. Overall, empathy interventions should be cautious of plausible adverse harms arising from overdrives of AE.